Development of Medicinal Plants Ethnobotany Study-Based Encyclopedia as Plantae Study Media - Hadiati, Devi; Retnoningsih, Amin; Widiatningrum, Talitha (Universitas Negeri Semarang, 2022)
The competence of plantae material is grouping plants' characteristics into divisions and linking their roles in life. This study aims to test the validity and effectiveness of the encyclopedia media for medicinal plants in Berastagi and Desa Pantai Labu, North Sumatra. Research methods and development of medicinal plants encyclopedia using the model analysis, design, development, implementation, and evaluation. The medicinal plants' encyclopedia was developed from the plant exploration research results, which were then validated and readability tests. The trial was conducted at SMA N 16 Medan using one control class (without an encyclopedia) and one experiment class (using an encyclopedia and textbooks). The exploration and identification of medicinal plant species in Berastagi and Pantai Labu Village found 30 species of medicinal plants belonging to 17 families. The characteristics of the encyclopedia of medicinal plants include images in the encyclopedia from the research results in the form of identification and inclusion of scientific names, local names, and the benefits of medicinal plants. The validation of media experts is 98%, and material experts are 95% with very valid criteria. The media readability test is 90.50% with easy-to-understand standards. The media's effectiveness in the cognitive aspects of the experiment class was higher than the control class, namely by 90% with very effective criteria. Classical mastery of the experiment class's psychomotor aspects and affective aspects was 100% with very effective criteria.